Dấu ấn Hồ Chí Minh trong các đại hội của Đảng cộng sản Việt Nam - Hoàng, Thị Thu Huyền (Tạp chí giáo dục và xã hội, 2023)
The birth and development of the Communist Party of Vietnam is associated with the great role and merits of President Ho Chi Minh. Starting with the Party Founding Conference in 1930, up to now, the Party's "golden historical phoenix has had 13 sacred "milestones, namely 13 National Congresses. President Ho Chi Minh has always been the "soul" of all congresses that have taken place in the more than 90-year history of growth and